2013
DOI: 10.2478/acph-2013-0038
|View full text |Cite
|
Sign up to set email alerts
|

Cytoprotective potential of anti-ischemic drugs against chemotherapy-induced cardiotoxicity in H9c2 myoblast cell line

Abstract: To investigate potential prevention or attenuation of anti- cancer drug induced cardiotoxicity using anti-ischemic drugs, a rat myoblast (H9c2) cell line was used as our in vitro cardiac model. Irinotecan and doxorubicin were found to be cytotoxic for the H9c2 cell line with IC50 of 30.69 ± 6.20 and 20.94 ± 6.05 mmol L-1, respectively. 5-Flurouracil and cladribine were not cytotoxic and thus IC50 could not be calculated. When 100 mmol L-1 doxorubicin was incubated for 72 hours with 50 mmol L-1 diltiazem, 100 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Our data are also in a consistent with Feridooni et al who found potential prevention or attenuation of anti-cancer drug-induced cardiotoxicity (Irinotecan and DOX) by using anti-ischemic drugs (losartan and DIL) plus dexrazoxane in (H9c2) rat cardiomyoblast cell line. They found that losartan and DIL were as effective as dexrazoxane in protecting the cardiac cells against irinotecan- and DOX-induced toxicity [32].…”
Section: Discussionmentioning
confidence: 99%
“…Our data are also in a consistent with Feridooni et al who found potential prevention or attenuation of anti-cancer drug-induced cardiotoxicity (Irinotecan and DOX) by using anti-ischemic drugs (losartan and DIL) plus dexrazoxane in (H9c2) rat cardiomyoblast cell line. They found that losartan and DIL were as effective as dexrazoxane in protecting the cardiac cells against irinotecan- and DOX-induced toxicity [32].…”
Section: Discussionmentioning
confidence: 99%
“…Among the inhibitors of RAAS overactivation, angiotensin-II receptor blockers (ARBs) are widely used drugs to prevent the progression of chronic heart failure in various comorbidities [17,18]. ARB losartan showed cardioprotective effects against experimental DOXO-induced cardiotoxicity [19,20]. Indeed, based on the results of clinical trials, inhibition of RAAS overactivation with ARBs has also shown beneficial effects on the development of DOXO-induced chronic cardiotoxicity [13].…”
Section: Introductionmentioning
confidence: 99%